2020
DOI: 10.25259/jcis_98_2020
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Bilateral Adrenal Radiofrequency Ablation in Severe Adrenocorticotropic Hormone-dependent Cushing Syndrome

Abstract: Objectives: The objectives of the study were to evaluate adrenal radiofrequency ablation (RFA) as a method of treatment in patients with severe adrenocorticotropic hormone (ACTH)-dependent Cushing syndrome, among whom bilateral adrenalectomy is not a suitable option. Material and Methods: Five patients with ACTH-dependent Cushing syndrome underwent RFA of both adrenal glands. Four of them presented with Cushing disease unsuccessfully treated with pituitary surgery and medical therapy, while one patient had A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Developed AI postoperatively. Body weight reduction, blood pressure normalization, bone mineral density improvement at 18-24 months [12] . 48 Female CD 2020, Poland TSS (x1), Cyber Knife Radiofrequency ablation Serum cortisol decreased from 1001.4 to 267.6.…”
Section: Discussionmentioning
confidence: 99%
“…Developed AI postoperatively. Body weight reduction, blood pressure normalization, bone mineral density improvement at 18-24 months [12] . 48 Female CD 2020, Poland TSS (x1), Cyber Knife Radiofrequency ablation Serum cortisol decreased from 1001.4 to 267.6.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this review also found promising results for RFA and MWA in metastatic adrenal tumors, in which the presence of residual tumor following ablation was seen in <25% of cases with <25% recurrence rates [ 123 ]. RFA has also shown to be promising in patients with severe adrenocorticotropic hormone (ACTH)-dependent Cushing syndrome for which bilateral adrenalectomy is not a suitable option [ 123 , 127 ]. A small case-series showed that all five patients who underwent bilateral RFA under CT-guidance had technical success with a resolution of their hypercortisolemia [ 127 ].…”
Section: Primary and Metastatic Adrenal Tumorsmentioning
confidence: 99%
“…RFA has also shown to be promising in patients with severe adrenocorticotropic hormone (ACTH)-dependent Cushing syndrome for which bilateral adrenalectomy is not a suitable option [ 123 , 127 ]. A small case-series showed that all five patients who underwent bilateral RFA under CT-guidance had technical success with a resolution of their hypercortisolemia [ 127 ].…”
Section: Primary and Metastatic Adrenal Tumorsmentioning
confidence: 99%
“…In all patients, there was a resolution of hypercortisolaemia, as well as Cushingoid clinical features following ablation. However, there is no long-term follow-up of disease recurrence [ 69 ]. Adrenal thermal ablation of phaeochromocytoma has had variable success.…”
Section: Adrenal Ablation: Current Clinical Evidencementioning
confidence: 99%
“…High quality supporting evidence for the use of adrenal ablation is not yet available and as such randomized controlled trials and direct head-to-head comparisons with surgery are necessary to fully evaluate its benefit. Undoubtedly thermal ablation offers promise to increase the scope for delivery of definitive therapy for adrenal endocrinopathies in unilateral and perhaps bilateral disease [ 24 ▪▪ , 69 , 79 ]. However, significant challenges remain in the development of the technology.…”
Section: Future Directions For Thermal Ablation Of Adrenal Disordersmentioning
confidence: 99%